Efecto de la aplicación de cobertores orgánicos y abonos verdes en propiedades fisicoquímicas y biológicas del suelo - González Aguirre, Janeth Kateherine (2019)
The objective of the current research work was to evaluate the application of organic covers on edaphic parameters and yield of two vegetables, as well as the effect of the incorporation of green manures into edaphic properties of the soil. Two trials were implemented in completely randomized designs. In the first trial three organic covers will be used: rice husk, “taralla”, cane bagasse and a control. In the second trial, six treatments of green manures were evaluated with four repetitions, which were: lablab-bean, lablab-bean + oat, chavelo bean, chavelo bean + oat, percal bean, percal bean + oat. The variables evaluated in the soil were: organic matter, cation exchange capacity, texture, pH, hydrophysical constants; while in the plants they were dry matter, weight of foliar mass, nitrogen, phosphorus, potassium, calcium, manganese, iron, zinc, and copper. Organic matter increased by 1.1% in treatments containing “taralla” and bagasse as covers; while in fertilizers the increase of 0.7% changes other soil characteristics of the soil such as: the pH that decreases from 5.8 to 5.3 and from 6.9 to 5.07; cation exchange capacity increased from 5.3 cmol/kg to 7.9 cmol/kg in organic covers and 4.7 cmol/kg to 8.1 cmol/kg in green manures; total nitrogen increased from 50 ppm to 90 ppm in organic covers and from 70 ppm to 140 ppm in green manures; Specific phosphorus content from 59 ppm to 89 ppm in organic covers and decreased from 103 ppm to 30 ppm in green manures. Taralla and bagasse are the most recommended organic covers to increase the organic matter content due to low C/N ratio and its rapid decomposition that allows to improve soil conditions in a short time. On the contrary, if it is required to maintain the humidity and avoid the growth of weeds, it is recommended to use rice husk since it is denser and prevents the penetration of light into the soil. As for green manures, the treatment that significantly improved the content of nitrogen, phosphorus, potassium, was the treatment where lablab-bean is found; However, mayor content of fresh and dried biomass were registered in treatments containing percal and chavelo bean. Keywords: production, covers, green manures, edaphic properties.